Effect of the spider toxin Tx3-3 on spinal processing of sensory information in naive and neuropathic rats: an in vivo electrophysiological study. (July 2017) - Dalmolin, Gerusa D.; Bannister, Kirsty; Gonçalves, Leonor; Sikandar, Shafaq; Patel, Ryan; Cordeiro, Marta do Nascimento; Gomez, Marcus Vinícius; Ferreira, Juliano; Dickenson, Anthony H.
Abstract: Introduction: Drugs that counteract nociceptive transmission in the spinal dorsal horn preferentially after nerve injury are being pursued as possible neuropathic pain treatments. In a previous behavioural study, the peptide toxin Tx3-3, which blocks P/Q- and R-type voltage-gated calcium channels, was effective in neuropathic pain models. Objectives: In the present study, we aimed to investigate the effect of Tx3-3 on dorsal horn neuronal responses in rats under physiological conditions and neuropathic pain condition induced by spinal nerve ligation (SNL). Methods: In vivo electrophysiological recordings of dorsal horn neuronal response to electrical and natural (mechanical and thermal) stimuli were made in rats under normal physiological state (naive rats) or after the SNL model of neuropathic pain. Results: Tx3-3 (0.3–100 pmol/site) exhibited greater inhibitory effect on electrical-evoked neuronal response of SNL rats than naive rats, inhibiting nociceptive C-fibre and Aδ-fibre responses only in SNL rats. The wind-up of neurones, a measurement of spinal cord hyperexcitability, was also more susceptible to a dose-related inhibition by Tx3-3 after nerve injury. Moreover, Tx3-3 exhibited higher potency to inhibit mechanical- and thermal-evoked neuronal response in conditions of neuropathy. Conclusion: Tx3-3 mediated differential inhibitory effect under physiological and neuropathic conditions, exhibiting greater potency in conditions of neuropathic pain. Abstract : The P/Q- and R-type voltage-gated calcium channel blocker Tx3-3 inhibits dorsal horn neuronal response of rats with greater potency after nerve injury.